Ancient genomes reveal trans-Eurasian connections between the European Huns and the Xiongnu Empire - Guido Alberto Gnecchi-Ruscone; Zsófia Rácz; Salvatore Liccardo; Juhyeon Lee; Yilei Huang; Luca Traverso; Rita Radzeviciute; Zsuzsanna Hajnal; Anna Szécsényi-Nagy; Balázs Gyuris; Orsolya Mateovics-László; Zsolt Bernert; et al. (Proceedings of the National Academy of Sciences, 2025)
The Huns appeared in Europe in the 370s, establishing an Empire that reshaped West Eurasian history. Yet until today their origins remain a matter of extensive debate. Traditional theories link them to the Xiongnu, the founders of the first nomadic empire of the Mongolian steppe. The Xiongnu empire dissolved, however, ~300 y before the Huns appeared in Europe, and there is little archaeological and historical evidence of Huns in the steppe during this time gap. Furthermore, despite the rich 5th to 6th centuries current era (CE) archaeological record of the Carpathian Basin, the cultural elements of connections with the steppe are limited to few findings and even fewer solitary eastern-type burials. In this study, we coanalyze archaeological evidence with 35 newly sequenced and published genomic data for a total of 370 individuals—from 5th to 6th century CE contexts in the Carpathian Basin including 10 Hun-period eastern-type burials, 2nd to 5th century sites across Central Asia and 2nd c. before current era (BCE) to 1st c. CE Xiongnu period sites across the Mongolian steppe. We find no evidence for the presence of a large eastern/steppe descent community among the Hun- and post-Hun-period Carpathian Basin population. We also observe a high genetic diversity among the eastern-type burials that recapitulates the variability observed across the Eurasian Steppe. This suggests a mixed origin of the incoming steppe conquerors. Nevertheless, long-shared genomic tracts provide compelling evidence of genetic lineages directly connecting some individuals of the highest Xiongnu-period elite with 5th to 6th century CE Carpathian Basin individuals, showing that some European Huns descended from them.